Vibration reduction of delta robot based on trajectory planning. (November 2020) - Wu, Mingkun; Mei, Jiangping; Zhao, Yanqin; Niu, Wentie
Highlights: The elastodynamics model is established based on KED method. Elastodynamics, rigid body dynamics and trajectory planning of the robot are integrated. A universal method to improve the precision of flexible robot is proposed. Abstract: In this paper, trajectory planning is used to suppress vibration of the Delta robot. Firstly, elastodynamic model of the Delta robot based on KED (Kineto-Elastic-Dynamic) method, substructure synthesis technology and Lagrange equation while considering the flexibility of the links, joints and reducers is built. Secondly, the trajectory planning is performed using polynomial function in the operating space, and its influence on output torque of three motors and elastic deformation of the moving platform is analyzed. Based on these, a comprehensive optimization objective is proposed for trajectory optimization, which is to minimize the maximum absolute elastic deformation and the mean absolute elastic deformation of the moving platform in two directions. Meanwhile, output torque of three motors is constrained. Finally, an optimal trajectory with minimum vibration is solved in the operating space. Results show that the optimal trajectory can effectively reduce elastic deformation of the moving platform.